Evaluation of background ionizing radiation in private tank farms in Port Harcourt - Aman, Gogo Fred; Avwiri, Gregory Onomakere (Faculty of Natural and Applied Sciences Journal of Scientific Innovations, 2023)
A Geographical positioning system (GPS) based in-situ measurement of background ionizing radiation of two private tank farms in Port Harcourt was conducted using well-calibrated radiation meters (Digilert–50 and Radalert-100). In each of the tank farms, eleven sampling points were randomly identified and the exposure rate was measured within each geographical location. The exposure rate measured in tank farm one (1) ranges from 0.010 ± 0.003 mRh-1 to 0.028 ± 0.004 mRh-1 with an average value of 0.019 ± 0.003 mRh-1 while that of tank farm two (2) ranges from 0.011 ± 0.001 mRh-1 to 0.021 ± 0.008 mRh-1 with an average value of 0.016 ± 0.005 mRh-1. The mean absorbed dose, annual effective dose equivalent (AEDE) and excess lifetime cancer risk (ELCR) in tank farm 1 are 137.6±9.80 nGyh-1, 0.211± 0.018 mSvy-1 and 0.738 ± 0.053 x 10-3 while the mean absorbed dose, AEDE and ELCR in tank farm 2 are 143.2±7.28 nGyh-1, 0.220± 0.019 mSvy-1 and 0.738 ± 0.053 x 10-3 respectively. The absorbed dose, Annual effective dose equivalent and excess lifetime cancer risk in tank farm 1 and tank farm 2 when compared with the united nation scientific committee on the effect of atomic radiation (UNSCEAR) standard of 84.0 nGyh-1, 1.0 mSvy-1 and 0.29 x 10-3 exceeded the permissible limit of absorbed dose and excess lifetime cancer risk while the value for AEDE is within the world safe value. The overall result shows that the background ionizing radiation level of the two tank farms has been elevated above safe values.